PENTINGNYA SARAPAN PAGI DALAM MENUNJANG KONSENTRASI BELAJAR SISWA DI SEKOLAH (Jurnal Tata Kelola Pendidikan, 2020)
Learning concentration is one of the important thing in student learning success.Concentration is needed to understand the material delivered by the teacher. One factorthat supports concentrate is breakfast. Although it’s often ignored or underestimated, butactually it the main support of the brain to improve concentration of learning. Skippingbreakfast can cause lethargy, weakness, dizziness and drowsiness. It causes a decrease ordifficulty in concentrating during school learning activities. So breakfast is needed becauseit can improve concentration of learning.
Keywords: Breakfast; Learn; Concentrate